Hubungan Antara Stabilitas Emosi dan Kualitas Pertemenan pada Siswa/I SMKS Dhuafa Padang - Deava Oktaviani Hidayat; Assyifaa Herbi Nuari; Calvina Izumi; Gita Jantika; Annisa Nadya Evelina; Izzanil Hidayati (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
In the development of adolescent emotional stability, there is a huge contribution from the friendship environment. The ability of adolescents to strengthen interpersonal relationships with peers cannot be separated from stability in their emotions. The majority of adolescents in Indonesia have good quality friendships and are equal to maintaining their friendships, Participants in this study were students at SMKS Dhuafa Padang whose average age was 15-18 years. This research is quantitative by using the Emotional Stability and Friendship Qualities Scale so that it can find a correlation between these two constructs or variables. In this study, the data analysis used was Pearson correlation analysis by showing the coefficient r = 0.427 with a significance value of <0.001 (P <0.05). These results indicate that there is a relationship between emotional stability and friendship quality. That is, the higher the quality of friendship, the better emotional stability.